Urban Farming-Based Learning: A Community Engagement Model for Agricultural Vocational Schools - Septyani, Ika Ayu Putri; Zamzami, Lutfi Fadilah; Sari, Novi Fitriandika (Universitas Ahmad Dahlan, 2025)
Background: Agriculture in the modern era faces increasingly complex challenges that require innovative and sustainable solutions. Contribution: Students on SMK Negeri 2 Rantauprapat lacked comprehensive understanding and hands-on exposure to modern methods such as aquaponics, hydroponics, and integrated urban farming systems. Method: This study applied a participatory action research approach designed to evaluate students baseline understanding, measure knowledge improvement, and enhance practical skills in sustainable agriculture through an urban farming-based community engagement program at the Vocational School of Agriculture Labuhanbatu (SMK Negeri 2 Rantauprapat). Results: Through training and community activities including collaborative pond construction, establishment of a hydroponic house, and development of a biofilter system students acquired both theoretical and practical skills. The initiative also fostered teamwork and a sense of ownership. Evaluation confirmed its effectiveness, as knowledge levels surged from pre-test benchmarks to over 70%, and even exceeded 90% in some areas. Conclusion: The evaluation results directly reflect the study's novelty. The survey on student interest revealed a very positive response, with more than 80% expressing strong interest in integrating urban farming and aquaponics into the curriculum, building facilities, and pursuing entrepreneurship. This high level of engagement underscores the effectiveness of the program's novel approach in bridging theory, practice, and community implementation.